Implementasi Smart Farming pada Budidaya Jamur Tiram - Y, Alauddin; Suwardoyo, Untung; Jasmawati, Jasmawati; Wirawan, Raden (Jurnal Mosfet, 2025)
The background of this research is the oyster mushroom cultivation process where people often have difficulty regulating temperature and humidity because these values change frequently, so people often have to monitor where the mushrooms grow to check the temperature and humidity. The purpose of this research is to make it easier for oyster mushroom farmers to monitor and control normalizing temperature and humidity by means of automatic watering and wider ventilation openings, this is done via the website by sending data from NodeMCU to a realtime database. The results of the research conducted show that the steam pump will automatically turn on if the DHT11 sensor detects a temperature of 28ºC or 60% humidity. The pump will automatically stop watering when the normal temperature is 22ºC-28ºC or humidity is 60%-70%. Vents will automatically open when the temperature is 22ºC or humidity is 70%. The vents will remain closed when the temperature is 22ºC or 60% humidity. Apart from watering, this system can also monitor the temperature and humidity status of the kumbung in real time through the website by sending data via firebase.